Does the additional use of clomiphene citrate or letrozole for in vitro fertilization deserve more attention? - Ying Liang; Qing Guo; Xiao-Hua Wu; Li-Nan Zhang; Jun Ge; Mei-Ling Xu; Zheng-Li Feng; Xiao-Qian Wu (BMC, 2021)
Abstract Background Adding clomiphene citrate (CC) and/or letrozole (LE) to in vitro fertilization (IVF) cycles for mild ovarian stimulation is a general approach. Although lots of researches have demonstrated partial benefits of the strategy, all-around effects of oral medications remained deficient. This paper aims to assess whether an addition of oral medication will result in considerable outcomes on T-Gn (total dose of gonadotropin), Gn days, total retrieved ova, high quality embryos, blastocyst number, ovarian hyperstimulation syndrome (OHSS) rate, clinical pregnancy rate and cumulative pregnancy rate, even if it was not conventional mild/minimal stimulations. Results Participants were categorized to three diverse populations as high responders, normal responders and poor responders according to basal antral follicle count. T-Gn in patients treated with CC/LE distinctly decreased from 2496.96 IU/d to 1827.68 IU/d, from 2860.28 IU/d to 2119.99 IU/d, and from 3182.15 IU/d to 1802.84 IU/d, respectively. For high ovary responders and normal responders, the OHSS incidence rate also declined from 29.2 to 4.3% (P < 0.001) and from 1.1 to 0.0% (P = 0.090). Other, there was no statistical difference with respect to the T-retrieved ova (total retrieved ova), high quality embryos, cultured blastocyst and blastocyst number in high responders. For normal responders and poor ovary responders, T-Gn, Gn days, T-retrieved ova, high quality embryos, cultured blastocyst and blastocysts number in oral medications group all apparently decreased. Clinical pregnancy rate per fresh cycle of poor responders with prior oral medications was significantly decreased (25.7% vs. 50.8%, P = 0.005), and no significant differences in high responders and normal responders were expressed (52.5% vs. 44.2%, P = 0.310; 51.9% vs. 42.4%, P = 0.163) between two groups of participants. The numbers of cumulative pregnancy rates were lower in the conventional group compared to the add group for high (75.90% versus 81.03%, P = 0.279), normal (62.69% versus 71.36%, P = 0.016) and poor (39.74% versus 68.21%, P < 0.001) responders. Conclusions The addition of CC/LE to the ovulation induction during IVF has certain efficacy in terms of low cost, low OHSS incidence. CC/LE deserves more recommendations as a responsible strategy in high responders due to advantageous pregnancy outcomes. For normal responders, the strategy needs to be considered with more comprehensive factors.